Pemanfaatan Firebase Realtime Database Dalam Perancangan Aplikasi Penilaian Siswa SMK Negeri 2 Pangkep Secara Realtime - Suradi, Andi Asvin Mahersatillah; Syam, Asrul; Alam, Samsu; Bahtiar, Akbar; M, Andrew Ridow Johanis (Yayasan Kita Menulis, 2024)
This research aims to design and develop an application for recording student grades at SMK Negeri 2 Pangkep using the Firebase Realtime Database to increase efficiency in data management, replacing the manual method that has been used using paper. The application development method applied is the Software Development Life Cycle (SDLC) which provides a structured and organized approach in every stage of development, from planning to maintenance. The advantages of SDLC include better risk management, strict quality control, and increased transparency throughout the development process. The results of this research were obtained through black box testing which showed the application ran well and was responsive, and made it easy for teachers to use. With the implementation of this application, it is hoped that it can speed up and simplify the process of recording student grades, bringing significant benefits in data management in the educational environment of SMK Negeri 2 Pangkep.